Teaching profession pressure at the basic education schools in the Sultanate of Oman = الضغوط المهنية لدى المعلمين بمدارس التعليم الأساسي في سلطنة عمان - Al Dafri, Saada Hashil; Ahmed Mohamed, Ismaiel Hassanein (International e-Journal of Advances in Social Sciences, 2020)
This quantitative study discusses the teaching profession pressures of life skills subject at basic education schools in the Sultanate of Oman. The problem lies in the large number of pressures, which is summarized in the multiplicity of his curriculum, and the division of evaluation methods and methods of their application, in addition to the numerical density taught by one teacher, which exceeds five hundred students often. The study aimed to discuss the work pressures most affecting teachers professionally and in study. It also sought to analyze the study sample's proposals in order to reduce the work pressures that teachers are exposed to professionally. The study used the descriptive approach in order to reach its goals, as it is the appropriate method for collecting quantitative and qualitative information and analyzing it accurately. The study was applied to a sample of (306) teachers and teachers, according to a questionnaire consisting of (35) paragraphs distributed over five axes that included: pressure Associated with students and the class environment, the pressures associated with physical (physical) working conditions, the pressures associated with the curriculum, the calendar, and the teaching methods, the pressures associated with the material return and the work system, and the pressures associated with parents and society. The findings revealed that; teachers suffer from pressures at work that ranged between high and medium, came at the forefront of a high-level pressure related to parents and society, followed by a high level pressures of material return, while the pressures of the curriculum, evaluation and teaching methods ranked last. The sample members suggested: increasing the number of teachers in some subjects to reduce pressure on teachers, developing curricula to keep pace with the requirements of modern and community life. ***************************************************************************** تناقش هذه الدراسة الكمية الضغوط المهنية لدى معلمين ومعلمات مادة المهارات الحياتية بمدارس التعليم الأساسي في سلطنة عمان. وتكمن المشكلة في كثرة الضغوط والأعباء الوظيفية الملقاة على عاتق معلم المهارات، التي تتلخص في تعدد المناهج الدراسية لديه، وتشعب أساليب التقويم وطرق تطبيقها، بالإضافة إلى الكثافة العددية التي يدرسها المعلم الواحد، والتي تزيد عن الخمسمائة طالب في كثير من الأحيان. هدفت الدراسة إل مناقشة ضغوط العمل الأكثر تأثيرا على المعلمين مهنيا ودراسيا، وتحليل مقترحات العينة للحد من ضغوط العمل التي يتعرض لها المعلمين. استخدمت الدراسة المنهج الوصفي من أجل الوصول إلى أهدافها، لكونه المنهج المناسب لجمع المعلومات الكمية والنوعية وتحليلها تحليلا دقيقا، وقد تم تطبيق الدراسة على عينة مكونة من (306) معلما ومعلمة، وفق استبانة تكونت من (35) فقرة موزعة على خمسة محاور شملت: الضغوط المرتبطة بالطلبة والبيئة الصفية، والضغوط المرتبطة بظروف العمل المادية (الفيزيائية)، والضغوط المرتبطة بالمنهج والتقويم وطرق التدريس، والضغوط المرتبطة بالعائد المادي ونظام العمل، والضغوط المرتبطة بأولياء الأمور والمجتمع. بينت النتائج: أن المعلمين يعانون من ضغوط في العمل تراوحت بين المرتفعة والمتوسطة، جاء في مقدمتها بمستوى مرتفع ضغوط تتعلق بأولياء الأمور والمجتمع، تلتها بمستوى مرتفع ضغوط العائد المادي، بينما احتلت ضغوط المنهج والتقويم وطرائق التدريس المرتبة الأخيرة. اقترح أفراد العينة: زيادة عدد المعلمين في بعض المواد الدراسية لتقليل الضغط على المعلمين، تطوير المناهج الدراسية لتواكب متطلبات الحياة العصرية والمجتمعية.